Center-based care and parenting activities - Jonas Jessen; Christa Katharina Spieß; Sevrin Waights (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We estimate effects of center-based care on parenting activities using time use data for Germany. Our estimates imply that center-based care reduces the overall time that parents spend with the enrolled child, but has only small negative effects on time spent doing activities together. Correspondingly, center-based care increases activities as a share of the time spent together with the child. The overall effect is driven by households with lower maternal education. Our findings imply that child development effects of center-based care may be explained, not just by the institutional environment, but also by changes that occur within the home environment.
Keywords: D13; I21; J13; 330; Child care; Child development; Time use; Parenting investments; Day care